A study on the perceived roles of nursing lecturers and clinical teachers at the faculty of medicine and health sciencs, UNIMAS in times of outbreak of emerging infectious disease - Lee, Shalin Wan Fei (Universiti Malaysia Sarawak (UNIMAS), 2008)
Nursing lecturers and clinical teachers were thought to be confined in colleges, universities and hospitals to teach and guide students. This study aims at identifying the role(s) of the nursing lectures and clinical teachers at FMHS, UNIMAS is contributing services to the country when a newly on re-emerging infectious disease strikes. In this study, two focus group sessions were carried out, with 5 nursing lecturers and 4 clinical teachers in the respective groups. Transcription of raw data into word-for-word quotations was done. Several themes emerged from the analysis of data. Among others, the role of acquiring knowledge on the disease, being the agents of mass media, volunteering, contributing their expertise and returning to the ward to help were significant. Participants also believed that they would withdraw the nursing students from infected areas, involving the nursing students into the situation, teaching the students and collaborating with various departments in research Being a novice researcher, managing focus groups was a problem. Nursing lectures and clinical teachers could contribute in the national preparedness plan. Further study on the roles of the nursing lectures and clinical teachers in times of outbreak of infectious is recommended.